2021
DOI: 10.3390/biology10050417
|View full text |Cite
|
Sign up to set email alerts
|

MiR-21 in the Cancers of the Digestive System and Its Potential Role as a Diagnostic, Predictive, and Therapeutic Biomarker

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs. They can regulate the expression of their target genes, and thus, their dysregulation significantly contributes to the development of cancer. Growing evidence suggests that miRNAs could be used as cancer biomarkers. As an oncogenic miRNA, the roles of miR-21 as a diagnostic and prognostic biomarker, and its therapeutic applications have been extensively studied. In this review, the roles of miR-21 are first demonstrated via its different molecular networks. Then, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 164 publications
(197 reference statements)
0
9
0
Order By: Relevance
“…Examination of miRNAs for specific fractions can significantly increase both the sensitivity and specificity of selected circulating miRNAs as noninvasive biomarkers [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Circulating Mirnamentioning
confidence: 99%
“…Examination of miRNAs for specific fractions can significantly increase both the sensitivity and specificity of selected circulating miRNAs as noninvasive biomarkers [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Circulating Mirnamentioning
confidence: 99%
“…To profile specific characteristics of multi-miRNAs in cancer-derived single EVs, three putative miRNA markers, miR-21, miR-122, and miR-375, , related to a wide range of cancers, were investigated as examples. Here, nanoflares and CHA amplification were integrated to achieve simultaneous and sensitive detection of EV multi-miRNAs (Scheme A).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, miR-21 * (32,33,35,49), miR-92a (30,34,46), miR-18a (39,42,49), miR-144 * (37,45,46), and miR-29a (34,42,43), which were the most studied miRNAs in this meta-analysis, were identified as possible non-invasive biomarkers for CRC. MiR-21-5p can regulate a variety of target genes and pathways involved in tumor growth, invasion, and metastasis, as well as play a significant role in 5-FU resistance and CRC cell radiosensitivity (53)(54)(55). Zhang et al demonstrated that miR-425-5p can influence chemoresistance in CRC cells through modulating programmed cell death (56).…”
Section: Discussionmentioning
confidence: 99%